Economic Crisis’s influence over the quantification of Puerto Rico’s Shadow Economy: Parsimonious Econometric Proposal - Castro-González, Segundo; Medina León, Julio C. (Journal of Applied Business and Economics, 2017)
This work proposes a model based on econometric technics, which through the use of Partial Least Squares-Structural Equation Modeling (PLS-SEM) achieves the quantification of Puerto Rico’s shadow economy in 2014. Using structural and internal consistency quality measures for reflective as for formative variables, the econometric model is optimized. The selected model with the best overall measures was denominated as MIMIC_UNE (6-2-1-3). This study has found that for 2014, the informal economy in Puerto Rico is of the order of 36.47% of the GDP, as the fact that it has been rising since 2000 up until this study’s date.